Leadership and organisation as a function of the different prevailing professional cultures - Lumpé, Marc-Philippe (Cranfield University, 2006)
The following research project develops leadership and organisational structures that are in accordance with the requirements created by different professional backgrounds. In order to do, that the theoretical construct Professional Culture is introduced. This construct unites the whole set of values, convictions and behavioural patterns that evolve within a common professional background. Further, Professional Culture is put into relation to its peer constructs of National and Organisational Culture. In a subsequent step, the different Professional Cultures and their characteristics are identified and appropriate leadership and organisational structures are proposed. This is undertaken with the help of an extensive empirical study and a broad literature review leading to the inclusion of a significant theoretical base into the study. In particular the so-called GLOBE-Study proved to be beneficial. The methodology used is based on both a quantitative and a qualitative approach in order to gain the maximum amount and quality of data possible. This methodology was employed in both a significant pilot study and the main study. The surveyed sample itself is composed of 196 respondents for the pilot study and 507 respondents from various organisations and countries for the main study which gives the study a sound empirical base. In total, twelve different Professional Cultures are isolated and characterised. These Professional Cultures include a vast variety of different occupations, stretching from Blue Collar Workers to Executive Management. An example for the differences in requirements encountered is the appropriate leadership style for blue collar workers and the one for executive management. Whereas the fon-ner explicitly favour a more steering and guiding leadership style, the latter prefer and need fteedom and inspiration by their leaders. Finally, a cross-evaluation is undertaken in order to validate the insights gained in the course of the research project. In summary, the following study gives a comprehensive overview of a number of different Professional Cultures and their characteristics , including their corresponding leadership and organisational structures.